Admission avoidance hospital at home - Edgar, K; Iliffe, S; Doll, HA; Clarke, MJ; Gonçalves-Bradley, DC; Wong, E; Shepperd, S (Cochrane Collaboration, 2024)
Background Admission avoidance hospital at home provides active treatment by healthcare professionals in the patient's home for a condition that would otherwise require acute hospital inpatient care, and always for a limited time period. This is the fourth update of this review.